Aplicativo web para el monitoreo del proceso de vinculación de la Universidad Nacional de Chimborazo utilizando la tecnología .Net. - Calderón Orozco, Joe Rodrigo (2025)
The present research work addressed the development of a web application aimed at monitoring the community engagement process of the National University of Chimborazo. The purpose of the research was to create a technological tool that allows for a structured visualization of the progress of this process over time, including key indicators such as the number of tutors, students, and active projects. During the development of the project, various technological tools were analyzed and used: ASP.NET for backend and frontend development, SQL Server as the database server, and Power BI to create reports interactively, facilitating real-time analysis and monitoring of process indicators. Additionally, the architecture pattern used was MVC (Model, View, Controller) and the agile Kanban methodology was adopted as the development methodology with the aim of dynamically adapting to any changes in requirements. The research adopted a quantitative approach, focused on the collection and analysis of statistical data obtained through usability tests applied to the users involved in the institutional process. These tests were conducted following the ISO 9241-11 standard, which establishes the three fundamental pillars of usability: effectiveness, efficiency, and satisfaction. Regarding the most relevant results to highlight: In the usability evaluation phase, users reported a high level of acceptance, the application's effectiveness reached 84.5%, efficiency 83.3%, and satisfaction 84.9%. These percentages demonstrated that the application meets the appropriate usability standards, thereby allowing for more efficient monitoring of engagement activities and improving access to information for decision-making.